The Effect of COVID-19 Infection During Pregnancy; Evaluating Neonatal Outcomes and the Impact of the B.1.1.7. Variant. Issue 12 (December 2021) - Murphy, Claire A.; O'Reilly, Daniel P.; Edebiri, Osasere; Donnelly, Jennifer C.; McCallion, Naomi; Drew, Richard J.; Ferguson, Wendy
Abstract : Background: Coronavirus disease 2019 (COVID-19) infection during pregnancy has been associated with adverse perinatal outcomes. We aim to evaluate the neonatal outcomes including the incidence of preterm birth, admission to the neonatal unit and incidence of congenital anomalies in this cohort. We will also describe these outcomes in the context of the B.1.1.7. variant outbreak, the dominant variant in Ireland since January 2021, which has had a greater impact on pregnant patients. Methods: This was a retrospective study of liveborn infants, delivered between 1st March 2020 and 1st March 2021, to women with a severe acute respiratory syndrome coronavirus 2 diagnosis during pregnancy, in a tertiary maternity hospital (8, 500 deliveries/year). Clinical data were collected, and analyses were performed to evaluate the impact of maternal symptom status, time from diagnosis to delivery and the B.1.1.7. variant on neonatal outcome. Results: In total 133 infants (1.6%) were born to women with severe acute respiratory syndrome coronavirus 2 identified during pregnancy. The median birth weight was 3.45 kg and gestational age at birth was 39.3 weeks. 14 infants (10.5%) were preterm. 22 infants (16.5%) required admission to the neonatal unit and 7 (5.3%) were small for gestational age. There was no difference in growth, preterm birth or neonatal unit admission based on maternal symptom status or infection after the outbreak of B.1.1.7. as the dominant strain. Conclusions: Following a COVID-19 infection in pregnancy, there was no increase in the incidence of preterm birth or neonatal intensive care unit admission compared with 5-year hospital data. Maternal symptom status did not influence neonatal outcomes. Further studies to evaluate the impact of COVID-19 in early pregnancy, the variants of concern, particularly the emerging Delta variant and COVID-19 placentitis are required.